Propuesta de redistribución de la planta de fundición de la empresa FUNDI LASER de la ciudad de Ambato - Morocho Guachagmi, Jimy Tobias (2024)
Currently, in the company FUNDI LASER, some problems have been identified in the area of Modeling and Foundry, such as clashes between lines or productive activities, expansion of the area, long times in each subactivity, excessive movements in the subprocesses which cause productivity is affected due to this; A Layout has been proposed as a proposal to redistribute the plant to improve the continuous workflow by eliminating the problems above. The flows of materials or people play a vital role in the production of the plant, hence the close relationship between the distribution approach and the selection of the means to materialize such flows, which will avoid waste in the process and waiting times., clashes between processes or activities, delays in the transportation of equipment and materials, etc. The Layout proposal for the company was worked using the SLP (Systematic Layout Planning) method of Richar Muther, in which it is proposed to improve the workflow due to the proper organization of the available production space, optimizing it based on the relationship that exists between each activity in the processes from start to finish to obtain quality products. To present the company's results, 3 possible alternatives were generated for the location of the existing machines and equipment at FUNDI LÁSER, in which you can see the relationship that exists between the 15 activities that are developed to produce round manhole covers that are produced in the company, the data obtained through calculations are entered into the CORELAP program, using a matrix the characteristics of a good Layout are identified; Among all the proposals, the first is selected, because it equitably distributes the product route and the entire production process can be seen, avoiding bottlenecks, but rather that the work route is distributed throughout the area, allowing us the integration of all the company's machinery, materials, human resources, and facilities, generating a large operational unit which works together effectively and seeking to minimize production costs to maximize productivity in the modeling and foundry area of the company.